PENGARUH KOMITMEN DAN MOTIVASI TERHADAP KINERJA KADER POS PELAYANAN TERPADU (POSYANDU) - Utik Bidayati (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
This study aimed to analyze the eï¬€ ect of commitment and motivation on the performance of health cadres in the village Sidomoyo, Godean, Sleman. The sample is determined by purposive sampling method. Data collected by providing a list of questions to respondents on aï¬€ ective commitment, commitment to sustainability, normative commitment, motivation and performance of health cadres. The results obtained indicate that all the variables committed no signiï¬ cant eï¬€ ect on performance. Only the motivation variable that has signiï¬ cant impact on the performance of cadres Yandu.